The wisdom of bones in search of human origins - Walker, Ian (Phoenix, 1996)
A groundbreaking book which leading on from the discovery of Homo Erectus, that this being was an animal trapped in a human body and had mastered the trick of growing a large brain. But to Walker's surprise the being was speechless, challenging the existing theory that the language acquisition marks the origins of man.